UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI SMA MODERN AL-RIFA’IE - Laili Noor Rochmah; Rosichin Mansur; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The purpose of this study is to describe the efforts of PAI teachers at Al-Rifa'ie Modern High School in shaping the character of students, so as to create students who have good character. The research method uses a qualitative approach because the data obtained are descriptive data. This type of research uses field research. Data was collected by using observation, interview and documentation methods. The data analysis technique in this study uses a data analysis technique model of Milles and Huberman by means of data collection, data reduction, data presentation and data verification or drawing conclusions. The audit of the results of this study was carried out with the diligence of the researcher, peer examination through discussion, and triangulation. Adapun hasil dari penelitian yakni guru PAI di SMA Modern Al-Rifa’ie secara garis besar memiliki dua upaya dalam pembentukan karakter, yang pertama upaya untuk pribadi guru dan yang kedua upaya untuk peserta didik. Adapun upaya untuk pribadi guru yakni upaya guru menjadi pribadi kunci dan menjadi guru yang mendidik dengan hati. Kemudian upaya guru untuk peserta didik yakni guru menggunakan metode dalam pembentukan karakter serta didik melalui pembiasaan-pembiasaan dalam kegiatan pembelajaran. Dengan melakukan pembiasaan maka peserta didik akan dibimbing dan diarahkan untuk terbiasa dan akan menjadi karakter di dalam diri peserta didik.